Grapevine Leafroll-Associated Virus 2 (GLRaV-2)- Mechanical Transmission, Purification, Production and Properties of Antisera, Detection by ELISA - Goszczynski, D.E.; Kasdorf, G.G.F.; Pietersen, G.; van Tonder, H. (South African Journal of Enology and Viticulture, 2017)
Grapevine leafroll-associated virus 2 (GLRaV-2) was transmitted from Vitis vinifera cv. Muscat d’Alexandrie to Nicotiana benthamiana following inoculation with grapevine leaf petioles extract concentrated by ultracentrifugation. Virus-infected N. benthamiana showed symptoms of chlorotic local lesions, systemic vein clearing followed by yellowing, stem necrosis and death of the plant. The plants were shown to be infected only with GLRa V-2. Antisera produced to GLRa V-2 strongly decorated particles of the virus in immunoelectron microscopy (IEM) and clearly and specifically detected GLRaV-2 in concentrated extracts of infected grapevines in Western Blots. The antisera were used with success for the specific and sensitive detection of GLRaV-2 by ELISA. Treatment of purified GLRaV-2 preparations with glutaraldehyde before immunisation markedly improved the quality of the antisera.